Problematika Program dan Implementasi Ekstrakurikuler di SMA Negeri dan Swasta di Kota Langsa - Legiman Legiman (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2019)
This study aims to uncover the program problems and extracurricular implementation in Langsa City High School. This research method uses a qualitative approach. The results showed that one of the problems of extracurricular activities at Langsa High School was that some students had not enjoyed the ideal extracurricular program offered and sought after. In extracurricular activities, there were diverse student disciplines, some of them were always absent, less enthusiastic about participating in activities. Extracurricular achievements have not been evenly distributed between high schools. Motivation and enthusiasm of students have not developed significantly. Not all high schools develop supporting factors for maximal extracurricular progress. Supervision and assessment have not been developed by the coach as a whole. Suggestions submitted are pleasing high schools in Langsa City, working together to develop quality programs and implementations for the development of students' interests and talents.